Consistent models for estimating chloride ingress parameters in fly ash concrete. (September 2015) - Muthulingam, S.; Rao, B.N.
Abstract: The addition of fly ash in cement or concrete is widely acknowledged to reduce chloride penetration and to enhance chloride binding capacity of cement paste fraction. This study proposes three parameter prediction models (submodels) of a chloride ingress model for fly ash concrete: time-variant surface chloride content; Langmuir and Freundlich isotherms constants; and reference chloride diffusion coefficient. The reliable evaluation of these submodels is essential to achieve more accurate estimation of the service life of concrete structures. Additionally, these submodels are required for physical modeling of coupled chloride-moisture transport in concrete. The comparison of chloride values between that estimated by incorporating submodels into the chloride ingress model with that from laboratory and field data show good agreement. The effects of submodel coefficients on the chloride ingress model are investigated through sensitivity analyses. Highlights: Inconsistencies in surface chloride, isotherm constant, and diffusion coefficient models are shown. Consistent parameter prediction models for chloride ingress into fly ash concrete are developed. Experimental validation for the developed models is performed with field and laboratory data. A sensitivity analysis of the developed model coefﬁcients is conducted.